Expression of interleukin 1-like cytokine interleukin 33 and its receptor complex (ST2L and IL1RAcP) in human pancreatic myofibroblasts. Issue 4 (8th December 2009) - Nishida, Atsushi; Andoh, Akira; Imaeda, Hirotsugu; Inatomi, Osamu; Shiomi, Hisanori; Fujiyama, Yoshihide
Abstract : Objective: Interleukin 33 (IL33) is a cytokine belonging to the IL1 family and it binds to a complex of the ST2L/IL1 receptor accessory protein (IL1RAcP). To define the role of IL33 in fibrogenesis of the pancreas, the expression of IL33, ST2L and IL1RAcP was examined in chronic pancreatitis tissues. The effects of IL33 on the functions of human pancreatic myofibroblasts were also investigated. Methods: Tissue samples were obtained surgically. The expression of IL33, ST2L and IL1RAcP was evaluated by standard immunohistochemical procedures. Messenger RNA expression for IL33, ST2L and IL1RAcP was analysed by northern blotting and real-time PCR analyses, and protein expression was assessed by western blotting and ELISA. Cell proliferation and migration were assessed by a 3 H-thymidine incorporation assay and the modified Boyden chamber assay, respectively. Results: IL33, ST2L and IL1RAcP were expressed by α-SMA-positive myofibroblasts in the fibrosis of chronic pancreatitis. In human pancreatic myofibroblasts, IL33 was weakly immunoexpressed without any stimuli, and this was markedly enhanced by IL1β, tumour necrosis factor α (TNFα) and lipopolysaccharide (LPS) via the mitogen-activated protein kinase (MAPK)-dependent AP-1 activation pathway. ST2L mRNA was weakly detected in unstimulated cells, and IL4 and interferon γ (IFNγ) strongly enhanced ST2L expression via STAT6 and STAT1 signalling, respectively. IL33 rapidly induced the phosphorylation of MAPKs and IκBα, and enhanced the expression of inflammatory mediators (IL6, IL8, IP-10, Gro-α, Gro-β and MCP-1) in IL4- or IFNγ-pretreated cells. IL33 stimulated the proliferation and migration of pancreatic myofibroblasts. Conclusions: IL33 and its receptor complex (ST2L and IL1RAcP) constitute a novel signalling system which may play an important role in the pathogenesis of chronic pancreatitis.